2018
DOI: 10.18820/24150487/as25i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of housing quality in Ibeju-Lekki periurban settlement, Lagos State, Nigeria

Abstract: This article assesses housing quality in IbejuLekki, a peripheral settlement outside Lagos metropolitan region. Using purposive sampling, 370 housing units from clusters of 16 periurban settlements constituted the sample size. Primary data was sourced through structured questionnaires, interview (with local planning personnel) and observation schedules administered through a field survey. Using Statistical Package for Social Sciences, data analysis was done using descriptive analysis to generate frequen cies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(28 reference statements)
1
6
1
Order By: Relevance
“…Notably, respondents were dissatisfied with the quality of their ceiling, ventilation, lightning, and the architectural design of their buildings. This finding contradicts Adedire and Adegbile, (2018) reporting good natural ventilation and lighting in most of the buildings in Ibeju-Lekki peri-urban settlement of Lagos Nigeria. One possible explanation for this variation is the locational differences of these settlements.…”
Section: 50 Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Notably, respondents were dissatisfied with the quality of their ceiling, ventilation, lightning, and the architectural design of their buildings. This finding contradicts Adedire and Adegbile, (2018) reporting good natural ventilation and lighting in most of the buildings in Ibeju-Lekki peri-urban settlement of Lagos Nigeria. One possible explanation for this variation is the locational differences of these settlements.…”
Section: 50 Discussioncontrasting
confidence: 89%
“…The dynamic relationship that exists between the physical features of housing, streets, open spaces and general settings in the neighbourhood determines neighbourhood quality (Adedire and Adegbile,2018). As stated by Clark & Huang, (2003) cited in Adedire and Adegbile (2018), neighbourhood quality is defined by the effects that neighbourhood characteristics have on a residence as a result of the environment in which it is located. Similar parameters are used to describe neighbourhood quality assessment criteria in Brkanić (2017).…”
Section: 20 Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Various typical studies in countries such as Nigeria (Adedire & Adegbile, 2018;Zunguzane, Smallwood & Emuze, 2012), Ghana (Ofori, 2020), and South Africa (Landman, Matsebe & Mmonwa, 2009) focus on user needs and expectations and play a part in determining the quality of residential environment and the performance of housing in general. Ibem et al (2012) revealed that, in Nigeria, Papua New Guinea and Ghana, respectively, residents were dissatisfied with the building features.…”
Section: Building Performance Evaluationmentioning
confidence: 99%